Модернизация конструкций отечественных турбогенераторов с учетом требований поддержания их конкурентоспособности - Шевченко, Валентина Владимировна; Минко, Александр Николаевич (НТУ "ХПИ", 2014)
В статье рассмотрены современные направления проведения модернизации турбогенераторов тепловых (в том числе атомных) электростанций. Предлагаемая модернизация рассмотрена для элементов и сборочных единиц неактивной зоны турбогенератора и ее предлагается проводить за счет использования современных технологий, применения новых материалов, использования современных систем охлаждения. Целью проведения работ является разработка предложений, которые смогут способствовать созданию отечественного турбогенератора, соответствующего уровню мировых стандартов.

The article describes the modern trends of the domestic power considering developments with the growing demand in the electricity, environmental requirements, provide turbogenerators opportunities manufacturing and transportation as the main generating capacity. The evaluation directions of turbogenerators modernization for thermal (including nuclear) power plants was carried out with a view to ensuring their competitiveness. The analysis showed that domestic turbogenerators inferior to the weight and size parameters of all international firms almost. And problem of optimizing the parameters inactive zone turbogenerators are especially acute. Therefore, in this paper we propose solutions to change the design of the inactive zone of the turbogenerator to reduce its weight and size parameters.
Modernization of nhe domestic turbogenerators constructors with the requirements to maintain their competitiveness
Keywords: турбогенераторы; модернизация; неактивная зона; система охлаждения; вибрация; массогабаритные показатели; turbogenerator; modernization; inactive zone; cooling system; vibration; weight parameters; size parameters